2006
DOI: 10.1007/s00418-006-0214-1
|View full text |Cite
|
Sign up to set email alerts
|

Cell death in development: shaping the embryo

Abstract: Cell death in animals is normally classified as type I (apoptotic), type II (autophagic) or necrotic. Of the biologically controlled types of death, in most embryos apoptosis is the most common, although in metamorphosis and in cells with massive cytoplasm type II is often seen, and intermediate forms are seen. For vertebrate embryos other than mammals, apoptosis is not seen prior to gastrulation but thereafter is used to sculpt the organs of the embryo, while overproduction of cells with subsequent death of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
88
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 62 publications
1
88
0
3
Order By: Relevance
“…By recycling these deoxyribonucleosides via the fast salvage pathway and reconverting them into dNTPs at a low ATP cost, rapidly dividing lymphocyte precursors may decrease their dependency on the slower and significantly more ATP demanding (4-fold) de novo synthesis. The analysis of the dCK KO mice shows that a similar requirement for active deoxyribonucleoside salvage does not seem to apply during embryogenesis, organogenesis, and tissue remodeling, processes that also involve high rates of proliferation and death (28). It remains to be determined whether dCK is required for the formation of germline cells.…”
Section: Why Do Developing Lymphocytes Depend On the Deoxyribonucleosidementioning
confidence: 99%
“…By recycling these deoxyribonucleosides via the fast salvage pathway and reconverting them into dNTPs at a low ATP cost, rapidly dividing lymphocyte precursors may decrease their dependency on the slower and significantly more ATP demanding (4-fold) de novo synthesis. The analysis of the dCK KO mice shows that a similar requirement for active deoxyribonucleoside salvage does not seem to apply during embryogenesis, organogenesis, and tissue remodeling, processes that also involve high rates of proliferation and death (28). It remains to be determined whether dCK is required for the formation of germline cells.…”
Section: Why Do Developing Lymphocytes Depend On the Deoxyribonucleosidementioning
confidence: 99%
“…Indeed, recent reports showed that basal autophagy plays an essential role in protein quality control in mammals, by continuously degrading misfolded or damaged proteins (Komatsu et al 2005(Komatsu et al , 2006Hara et al 2006), and prevents metabolic stress-induced genome instability and tumor progression (Mathew et al 2007). During development, high levels of autophagy may also contribute to some forms of programmed cell death, as in the case of degenerating larval tissues during insect metamorphosis (Butterworth and Forrest 1984;Neufeld 2004;Penaloza et al 2006).…”
mentioning
confidence: 99%
“…Ainsi, l'apoptose apparaît comme un processus cellulaire qui doit être finement régulé. Outre son rôle dans différents contextes pathologiques, l'apoptose est essentielle au cours du développement [2,3]. C'est d'ailleurs dans ce contexte qu'elle a été initialement identifiée chez des organismes modèles tels que le ver à soie et le têtard.…”
unclassified
“…Ces corps apoptotiques permettent une élimina-tion « propre » des cellules, sans déver-sement du contenu cellulaire à l'exté-rieur, et donc sans inflammation ; ils seront ensuite éliminés par les macrophages. Au cours du développement, l'apoptose permet de réguler le nombre de cellules au sein d'un tissu, mais aussi de sculpter différentes structures [2,3]. Parmi les diffé-rents modèles de morphogenèse dépendant de l'apoptose (coeur, intestin, mains), la formation des doigts chez les vertébrés a été très étudiée.…”
unclassified